A Portfolio Analysis of Straddle Operations in the Futures Markets: An Application of the Expected Returns-Variance of Returns Hypothesis - Schrock, Nicholas W. (Journal of Finance, 1969)
Nicholas W. Schrock, A Portfolio Analysis of Straddle Operations in the Futures Markets: An Application of the Expected Returns-Variance of Returns Hypothesis, The Journal of Finance, Vol. 24, No. 3 (Jun., 1969), pp. 547-548